2022
DOI: 10.1155/2022/2131125
|View full text |Cite|
|
Sign up to set email alerts
|

Sports Training Strategy and Interactive Control Method Based on Digital Twins and Wireless Sensor Networks

Abstract: By combining virtual reality, the digital twin system has been deeply applied in many places. Especially with the upsurge of national sports and more attention to sports, people have also begun a more in-depth study on the strategy of sports training. This paper aims to explore the application of the Brazilian jujitsu training strategy and interactive control method in the new era. Based on the sports skills of Brazilian jujitsu, combined with digital twin technology and wireless sensor network technology, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The continuing aging of society will further increase the number of disabled individuals. With the development of the social economy, sensory and cognitive functions have been lost or damaged, and the number of people suffering from severe diseases due to aging continues to rise each year (He & He, 2022). Research reports demonstrate that active rehabilitation training for serious disabling diseases, such as heart and brain diseases, can allow 90% of patients to recover their ability to walk and take care of themselves, while 30% of patients can resume some light work.…”
Section: Introductionmentioning
confidence: 99%
“…The continuing aging of society will further increase the number of disabled individuals. With the development of the social economy, sensory and cognitive functions have been lost or damaged, and the number of people suffering from severe diseases due to aging continues to rise each year (He & He, 2022). Research reports demonstrate that active rehabilitation training for serious disabling diseases, such as heart and brain diseases, can allow 90% of patients to recover their ability to walk and take care of themselves, while 30% of patients can resume some light work.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors offer valuable means of quantifying an athlete's movements, which can be challenging to observe and measure with the naked eye, especially considering the quick movements in some sports. By capturing precise data on forces, accelerations, and other relevant metrics, coaches and athletes can make informed decisions regarding training adjustments, injury prevention, and performance optimization ( 4 ). Wireless connectivity for health and sports monitoring using Bluetooth and Zigbee to collect data unobtrusively without hindering movement has been proven to work great for measuring athlete performance ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%